ANALYSIS OF THE GREEN VALUE CHAIN AND ITS ROLE IN REDUCING COSTS AND IMPLEMENTING THE STRATEGY OF CLEANER PRODUCTION PERFORMANCE (APPLIED STUDY IN THE KUFA CEMENT FACTORY) (World Economics and Finance Bulletin, 2022)
The current research aims to address the theoretical framework of the green value chain, and analyze this chain in order to reduce costs and implement the strategy of cleaner production performance, and implementing the strategy of cleaner production performance and improving indicators of both economic and environmental, efficiency, effectiveness and productivity. The research was applied in the Kufa Cement Factory / one of the formations of the General Company for the Iraqi Southern Cement Industry for the fiscal years 2018, 2019, 2020. One of the most important conclusions reached is that the research sample laboratory can analyze the green value chain in order to reduce costs, and its helps implement the strategy of cleaner production performance and improving indicators of both environmental economics, efficiency, effectiveness and productivity
Keywords: Green value chain; analysis of green value chain analysis; reduce costs; strategy